(untitled) (IIUC Business Review, 2021)
Time and cost are two remarkable elements prescriptive of success in project management. The anticipated project length may go over the desired period in many projects. Therefore, it becomes vital to shorten the critical path in order to finish the project by the goal date. Time-cost trade-off (TCT) in project network, the reduction in time with a minimum cost of project activities, has increased efficiency of the project. To shorten a project duration activity crashing, which includes allocating additional resources to an activity with the objective of diminishing its duration, is the most commonly employed compression technique. The objective of an optimum solution of time-cost trade-off is to provide maximum profit opportunity with a minimum time. There are many algorithms (heuristic, meta-heuristic and exact) established in this regard. In this paper a constructive algorithm is proposed and implemented with a fairy application example to acquire optimum solution or close-optimum solution of TCT problems. IIUC Business Review Vol. 10, Dec. 2021 pp. 115-128